2011
DOI: 10.1152/ajpgi.00032.2010
|View full text |Cite
|
Sign up to set email alerts
|

Small intestine CD11c+CD8+T cells suppress CD4+T cell-induced immune colitis

Abstract: CD8ϩ T cells suppress CD4 ϩ T cell-induced immune colitis. Am J Physiol Gastrointest Liver Physiol 300: G939 -G947, 2011. First published March 24, 2011 doi:10.1152/ajpgi.00032.2010.-The large (LI) and small intestine (SI) differ in patterns of susceptibility to chronic mucosal inflammation. In this study, we evaluated whether this might, in part, reflect differences in resident mucosal CD11c ϩ T cells. These cells comprised 39 -48% (SI) and 12-17% (LI) of the intraepithelial compartment, most of which were T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…However, CD11c + CD8 + T cells-induced and expanded by inoculation of agonistic anti-4-1 BB mAb in collagen type II-induced arthritis mice (25), experimental autoimmune uveoretinitis mice (26), and hapten-induced colitis mice (27)- were found to be regulatory T cells that suppressed Ag-specific CD4 T cells through an IDO-dependent mechanism. In addition, CD11c + CD8 + T cells in small intestine, but not in large intestine, were recently identified as a distinct intestinal regulatory T cell population to control proinflammatory CD4 T cells and maintain intestinal mucosal homeostasis (28) …”
Section: Cd4mentioning
confidence: 99%
“…However, CD11c + CD8 + T cells-induced and expanded by inoculation of agonistic anti-4-1 BB mAb in collagen type II-induced arthritis mice (25), experimental autoimmune uveoretinitis mice (26), and hapten-induced colitis mice (27)- were found to be regulatory T cells that suppressed Ag-specific CD4 T cells through an IDO-dependent mechanism. In addition, CD11c + CD8 + T cells in small intestine, but not in large intestine, were recently identified as a distinct intestinal regulatory T cell population to control proinflammatory CD4 T cells and maintain intestinal mucosal homeostasis (28) …”
Section: Cd4mentioning
confidence: 99%
“…Although inflammation is seen primarily in the colon in this model, several recent studies have shown that regulatory cell induction in the small intestine is necessary to protect from colitis, leading us to further investigate this decrease in Tregs in the PP and small intestine. 32, 33 …”
Section: Resultsmentioning
confidence: 99%
“…Generally, intestinal CD11c + MHC class II + DCs can be divided into three major subsets; CD103 + CD11b 2 , CD103 + CD11b + , and CD103 2 CD11b + cells, and the functions of each subset are intensively analyzed in many studies (15,(28)(29)(30). In this study, we used CD11c-cre transgenic mice to examine the role of DCs and identified magnetically sorted CD11c + cells as DCs, although CD11c is reported to express on other immune cells such as CD8 + T cells in the intestine (31). TGF-b is an important cytokine in the pathogenesis of inflammatory diseases, including IBD (32).…”
Section: Discussionmentioning
confidence: 99%